2003
DOI: 10.1097/00003226-200305000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Encephalocraniocutaneous Lipomatosis: Case Report and Review of the Literature

Abstract: Regarding this case, we suggest adding aniridia to the possible ocular anomalies in this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“… References: (1) Ahmed et al [2002]; (2) Alfonso et al [1986]; (3) Almer et al [2003]; (4) Amor et al [2000]; (5) Andreadis et al [2004]; (6) Bamforth et al [1989]; (7) Brown et al [2003]; (8) Ciatti et al [1998]; (9) Chittenden et al [2002]; (10) Cultrera et al [2004]; (11) Deda et al [2001]; (12) Donaire et al [2005]; (13) Fishman et al [1978]; (14) Fishman [1987]; (15) Fitoz et al [2002]; (16) Gokhale et al [2007]; (17) Grimalt et al [1993]; (18) Haberland and Perou [1970]; (19) Happle and Steijlen [1993]; (20) Hauber et al [2003]; (21) Hennekam [1994]; (22) Jones [2006]; (23) Loggers et al [1992]; (24) Kodsi et al [1994]; (25) Lasierra et al [2003]; (26) Legius et al [1995]; (27) MacLaren et al [1995]; (28) Moog et al [2007]; (29) Nosti‐Martinez et al [1995]; (30) Nowaczyk et al [2000]; (31) Miyao et al [1984]; (32) Narbay et al [1996]; (33) Parazzini et al [1999]; (34) Pascual‐Castroviejo et al [2005]; (35) Rathoriya and Shrivastava [2006]; (36) Romiti et al [1999]; (37) Rubegni et al [2003]; (38) Sant'Anna et al [1999]; (39) Savage et al [1985]; (40) Sanchez et al [1981]; (41) Sofiatti et al [2006]; (42) Torrelo et al [2005]; (43) Valladares et al [2007]; (44) Walbaum et al [1979]; (45) Zielinska‐Kazmierska et al [2005]. …”
Section: Resultsmentioning
confidence: 99%
“… References: (1) Ahmed et al [2002]; (2) Alfonso et al [1986]; (3) Almer et al [2003]; (4) Amor et al [2000]; (5) Andreadis et al [2004]; (6) Bamforth et al [1989]; (7) Brown et al [2003]; (8) Ciatti et al [1998]; (9) Chittenden et al [2002]; (10) Cultrera et al [2004]; (11) Deda et al [2001]; (12) Donaire et al [2005]; (13) Fishman et al [1978]; (14) Fishman [1987]; (15) Fitoz et al [2002]; (16) Gokhale et al [2007]; (17) Grimalt et al [1993]; (18) Haberland and Perou [1970]; (19) Happle and Steijlen [1993]; (20) Hauber et al [2003]; (21) Hennekam [1994]; (22) Jones [2006]; (23) Loggers et al [1992]; (24) Kodsi et al [1994]; (25) Lasierra et al [2003]; (26) Legius et al [1995]; (27) MacLaren et al [1995]; (28) Moog et al [2007]; (29) Nosti‐Martinez et al [1995]; (30) Nowaczyk et al [2000]; (31) Miyao et al [1984]; (32) Narbay et al [1996]; (33) Parazzini et al [1999]; (34) Pascual‐Castroviejo et al [2005]; (35) Rathoriya and Shrivastava [2006]; (36) Romiti et al [1999]; (37) Rubegni et al [2003]; (38) Sant'Anna et al [1999]; (39) Savage et al [1985]; (40) Sanchez et al [1981]; (41) Sofiatti et al [2006]; (42) Torrelo et al [2005]; (43) Valladares et al [2007]; (44) Walbaum et al [1979]; (45) Zielinska‐Kazmierska et al [2005]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, 23 further patients are reviewed, all of whom meet Hunter’s criteria except one patient, who has been included because of his typical skin lesions 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53…”
Section: Methodsmentioning
confidence: 99%
“…However, nonsyndromic and isolated form of NP, firstly described and specifically named by Happle and Küster, in 1998 [4,8,11]. Chan et al have stated that, NP lesions were detected in 36 (97%) of previously reported 37 patients with ECCL until 2006 [12,13]. The hamartomatous scalp lesions include hairless or less-hairy, flat or dome shaped, usually skin-colored or yellowish, soft, mostly unilateral, and rarely bilateral masses [1][2][3]5] .…”
Section: Discussionmentioning
confidence: 99%